Access to academic and chairs for the Second Republic. The performance of Flores de Lemus in the Court faces opposition Viñuales Augustine and Francisco Bernis (icade. Journal of the Faculty of Law at Universidad Pontificia Comillas, 2012)
Between the end of 1932 and the beginning of 1933 took place in Madrid the public competitive examinations to win a chair in Public finance of the Central University. Two well-known economists aimed to win this chair: Francisco Bernis, with a large and solid scientific work, and Agustín Viñuales, who contributed with a single work, which is not certain to be written in his own hand writing. The board of examiners, of which Flores de Lemus and three of his disciples –Carande, Franco and Rodríguez Mata– were members, decided unanimously to propose Viñuales for thechair. Using the unpublished documentation of the opposition’s record and the information published in the press and the magazines of that time, the almost absolute control of Flores de Lemus, through his academic prestige and his powerful politic influence, is emphasized. He wielded his control over the access to theeconomy chairs during the first third of the twentieth century and, particularly, during the Republican Administration.
Keywords: economic history; university education; access to chairs